Candida auris Isolates of the Southern Asian and South African Lineages Exhibit Different Phenotypic and Antifungal Susceptibility Profiles In Vitro - Szekely, Adrien (J Clin Microbiol, 2019)
Candida auris is a serious nosocomial health risk, with widespread outbreaks occurring in hospitals worldwide. Sequence analyses of outbreak isolates revealed that C. auris has simultaneously emerged as four distinct continentally restricted clonal lineages. We previously reported multiple independent introductions of C. auris isolates from at least three of these lineages (the Southern Asia, South African, and Japanese/Korean lineages) into hospitals across the United Kingdom and that isolates circulating in the United Kingdom displayed two different cell phenotypes which correlated with differences in virulence in Galleria mellonella wax moths. Here, we compared the phenotypic characteristics and antifungal susceptibilities of isolates representative of the three geographic clades circulating in the United Kingdom. Isolates of the South African and Japanese/Korean lineages, but not those of the Southern Asian lineage, grew well on media containing actidione. However, unlike Southern Asian lineage isolates, they were unable to produce even rudimentary pseudohyphae in culture. Importantly, although all isolates were fluconazole resistant in vitro, fluconazole and voriconazole exhibited significantly higher MICs against isolates of the South African lineage than against isolates of the Southern Asian lineage. A similar trend was seen with minimum fungicidal concentrations (MFCs), with higher MFCs of the triazole antifungal agents being seen for the South African lineage isolates. Finally, the formation of large cellular aggregates was seen only with isolates of the South African and Japanese/Korean lineages, which correlates with the reduced virulence observed previously in Galleria wax moths inoculated with such isolates. Intriguingly, aggregation could be reversibly induced in isolates of the Southern Asian lineage by exposure to triazole and echinocandin antifungals but not by exposure to amphotericin B or flucytosine.